A flexible and holistic framework to bridge soil health gaps in the Global South. - Visscher, Anna M; Bongiorno, Giulia; Pulleman, Mirjam (2024)
• Key challenges associated with the measurement and interpretation (including benchmarking) of soil health indicators at scale; • The scarcity of empirical studies linking soil health indicators to agronomic and environmental outcomes, including trade-offs; • The need for robust, practical, and low-cost soil health protocols to support farmer decision making.